Shifting Power in Asia-Pacific? : The Rise of China, Sino-US Competition and Regional Middle Power Allegiance - Fels, Enrico (Springer, 2020)
Contents: Acknowlegements -- 1 Opening the Floor: The Rivalry Between Eagle and Dragon in Asia-Pacific -- 2 Theoretical Framework: Realism as a Lens for Analysis -- 3 Power in International Affairs -- 4 Towards a Middle Power Theory in International Affairs -- 5 Taking Stock of Asia-Pacific's Tangible Power Changes -- Measuring Aggregate Power -- 6 Determining the (Almost) Intangible: Measuring Relational Power -- 7 Australia -- Trading With the Dragon, But Flying With the Eagle -- 8 Pakistan -- "Iron Brother" to Beijing, Reluctant Partner for Washington -- 9 Japan -- Warm Ties to Washington, "Cold Politics" With Beijing -- 10 Republic of Korea -- No Longer a Small "Shrimp Among Whales" -- 11 Thailand -- Bending With the Wind Again? -- 12 Indonesia -- Rowing Between Two Reefs Once More -- 13 Conclusion -- Does "Rising" in Power Equate to "Shifting" of Power?.